Implementasi Rateb Siribee terhadap Akhlak Siswa Madrasah Aliyah Swasta Pondok Ulumul Quran Mardhatillah Tangga Besi Kota Subulussalam - Fitriyani Chaniago; Saifullah Idris; Masbur Masbur (Master's degree Department of Islamic Education Postgraduate Program of Universitas Islam Negeri (State Islamic University) Ar-Raniry, Banda Aceh in cooperation with Center for Research and Community Service (LP2M), 2023)
Morals occupy an important position in human life, both as individuals, communities, and nations. This article aims to find out how the implementation of Rateb Siribee on the morals of students at the Ulumul Quran Mardhatillah Islamic Boarding School Pondok Tangga Besi Kota Subulussalam. This type of research includes qualitative research. Primary data in this study are the results of interviews with several students and teachers at the Ulumul Qur'an Mardhatillah Islamic Boarding School Tangga Besi, Subulussalam District. Secondary data is obtained through a review of documentation derived from books, journals, related articles that become a foothold in the implementation of research. Data collection techniques in this study include observation, interviews, and documentation review. The data analysis technique used in this research is content analysis. The implementation of Rateb Siribe on the morals of Pasantren Ulumul Quran Tangga Besi Subulussalam City students is to educate students to become qualified individuals for their religion and nation. In particular, making students feel the existence of Allah directly in everyday life, then educating students in discipline, increasing worship and strengthening friendship.